Scientific revolutions and the structure of critical care - Papathanassoglou, Elizabeth (My University, 2006)
References to holism and holistic practice are increasing within the critical care nursing literature (Chulay et al., 1997; Muhlberg and Ruth-Sahd, 2004; Lane et al., 2005). Although the underpinning ideals of holism are often misinterpreted and equated with providing psychosocial care, this suggests that there is a need to reflect and expand our framework of practice and research in this field. This editorial will attempt to discuss evidence whether holism is relevant to modern critical care practice, to explore whether a major paradigm shift towards holism in critical care should be anticipated, or if it is happening, to discuss nursing factors that may hamper or, on the contrary, promote holistic practice
Keywords: Critical care nursing; Catastrophic illness; Evidence-based medicine; Nursing--Research; Psychophysiology; Intensive care nursing